A Pilot Phase II Study of the Efficacy and Biosafety of Doxorubicin Chemotherapy in Tumor‐Bearing Equidae. (20th September 2013) - Théon, A.P.; Pusterla, N.; Magdesian, K.G.; Wittenburg, L.; Marmulak, T.; Wilson, W.D.
<x xml:space="preserve">Abstract</x> Background The efficacy and biosafety of a previously established tolerable dosage of doxorubicin have not been established in horses. Objectives To provide preliminary evidence of the efficacy of doxorubicin in tumor‐bearing horses, explore drug pharmacokinetics profile, and estimate period of risk of exposure to drug residues. Animals Twelve horses with 37 tumors. Procedures Treatment protocol included 6 treatments at 3‐week intervals. Eight horses were uniformly treated at a dosage of 70 mg/m2 and 4 horses received 4 of 6 treatment cycles at 70 mg/m2. Clinical signs, tumor responses, and toxicoses were evaluated. Drug residue concentrations were quantitated in 3 horses receiving of 65, 70, and 75 mg/m2 by high‐performance liquid chromatography with ultraviolet detection (plasma, feces) and liquid chromatography and tandem mass spectrometry (urine). Results Thirty tumors, including lymphomas, carcinomas, sarcoids, and melanoma, were evaluated for efficacy. The overall response rate was 47% (95% CI, 28–65%). Doxorubicin was not found to be effective against melanomas. Lymphomas and carcinomas were most responsive. Pooled serum Cmax and half‐life of doxorubicin were 121.3 ng/mL and 12.9 hours, respectively. There were no detectable residues in fecal samples up to 3 weeks after treatment and in plasma and urine after 2 and 3 days, respectively. Conclusion and Clinical Relevance This study provides preliminary evidence that single‐agent doxorubicin at a dosage of 70 mg/m2 has a broad spectrum of activity. The risk of exposure to drug residues in plasma and feces was low. Direct contact with urine‐contaminated wastes should be avoided for 2 days after treatment.